He Ao Pohewa: The PHARMAC Prescription for Pharmacoeconomic Analysis in New Zealand and the Standards of Normal Science - Paul C Langley (University of Minnesota Libraries Publishing, 2016)
In common with a number of other single payer health systems, New Zealand has, through the Pharmaceutical Management Agency (PHARMAC), established guidelines for formulary submissions by pharmaceutical manufacturers. A question that is important to health system decision makers is to whether or not guidelines for economic evaluations in countries like New Zealand are consistent with the standards of normal science. Do the guidelines require those making the submission to put their claims in the form of testable hypotheses that can support falsification and replication? Are post-listing evaluations of these claims ever carried out? The purpose of this review is to consider whether the 2012 PHARMAC guidelines meet these standards. The assessment argues that the guidelines do not meet the standards of normal science. Instead, from this perspective, they are best characterized as supporting the creation of he ao pohewa (an imaginary world). There is no requirement in the guidelines for claims to be expressed as testable propositions; as hypotheses for expected impact that can be evaluated and the outcomes reported as part of ongoing disease area and therapeutic class reviews. There is no commitment to the discovery of new facts though falsification and replication. Our review concludes with suggestions for a reworking of the guidelines to meet the standards of normal science.   Type: Commentary